Anxiety symptom remission is associated with genetic variation of PTPRZ1 among patients with major depressive disorder treated with escitalopram. Issue 8 (1st June 2021) - Su, Yun-Ai; Bousman, Chad A.; Liu, Qi; Lv, Xiao-Zhen; Li, Ji-Tao; Lin, Jing-Yu; Yu, Xin; Tian, Li; Si, Tian-Mei
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: Genome-wide analyses of antidepressant response have suggested that genes initially associated with risk for schizophrenia may also serve as promising candidates for selective serotonin reuptake inhibitor (SSRI) efficacy. Protein tyrosine phosphatase, receptor-type, zeta-1 (PTPRZ1) has previously been shown to be associated with schizophrenia, but it has not been investigated as a predictor of antidepressant efficacy. The main objective of the study was to assess whether SSRI-mediated depressive and anxiety symptom remission in Chinese patients with major depressive disorder (MDD) are associated with specific PTPRZ1 variants. Methods: Two independent cohorts were investigated, the first sample ( N = 344) received an SSRI (i.e. fluoxetine, sertraline, citalopram, escitalopram, fluvoxamine, or paroxetine) for 8 weeks. The second sample ( N = 160) only received escitalopram for 8 weeks. Hamilton Depression and Hamilton Anxiety Rating Scale scores at 8-weeks post-baseline in both cohorts were used to determine remission status. Five PTPRZ1 variants (rs12154537, rs6466810, rs6466808, rs6955395, and rs1918031) were genotyped in both cohorts. Results: Anxiety symptom remission was robustly associated with PTPRZ1 rs12154537 ( P = 0.004) and the G–G–G–G haplotype (rs12154537–rs6466810–rs6466808–rs6955395; P = 0.005) in cohort 2 but not cohort 1 (mixed SSRI use). Associations with depressive symptom remission did not survive correction for multiple testing. Conclusions: These findings suggest that PTPRZ1 variants may serve as a marker of escitalopram-mediated anxiety symptom remission in MDD.